SPECTRUM OF HEPATOCELLULAR CARCINOMA AT SHIFA INTERNATIONAL HOSPITAL, ISLAMABAD - Khokhar, Nasir; Aijazi, Ishma; Gill, Muzaffar Latif (Journal of Ayub Medical College Abbottabad, 2003)
Background: The aim of this study was to review etiological and clinical features of patients with hepatocellular carcinoma (HCC) at a tertiary care centre in past nine years. Relevant data on HCC in other parts of country and world were reviewed. Methods: Patients who had biopsy proven HCC were reviewed retrospectively. Demographic features were noted and positivity for serology, presence of cirrhosis, level of alpha-fetoprotein, tumour size and distribution of liver lesions were noted. Results: A total of 67 patients were found to have biopsy proven HCC. Mean age was 58.64 ± 12.77 years. Males were 79%. Hepatitis B surface antigen was noted to be positive in 23% of the patients, who were tested and hepatitis C antibody was found to be positive in 67% of the patients who were tested. Alpha fetoprotein level was 632.09 ± 1332.31. Cirrhosis was noted in 69% patients. Tumour size in patients with single lesion was 6.6 ± 1.14 cm. Patients with single lesion had 70% time involvement of the left lobe and 30% times had involvement of the right lobe. Fifty one percent of the patients in this series had multilocular distribution. Conclusion: Hepatocellular carcinoma has become a common tumour in Pakistan and studies are showing that this cancer is related to hepatitis C virus infection in majority of the patients. A large number of them have underlying cirrhosis and are multifocal in origin and are presented in an advanced condition. Key words: Hepatocellular carcinoma, Hepatitis C, Hepatitis B, Alpha fetoprotein, Cirrhosis